Situational Analysis: Relevant Advances in Grounded Theory for Management Studies - Ássimos, Bruno Medeiros; Pinto, Marcelo de Rezende (Organizações & Sociedade, 2022)
This paper aims at closing a gap in literature referring to academic publications that approach grounded theory, considering that little advance has been noticed in discussions that encompass the application of situational analysis (SA) proposed by Clarke (2003, 2005) and Clarke, Friese and Washburn (2018) in management studies. Thus, this conceptual paper seeks to address situational analysis considering its ontological and epistemological aspects, to investigate its operationalization forms, and, finally, to indicate relevant situational analysis issues for management studies. Our discussion sheds light on relevant situational analysis aspects, which helps prioritizing research methods that may contribute to create fairer and more effective social policies in several fields and meeting daily demands of the management field. As a conclusion, situational analysis seems to bring new guidance to grounded theory after the interpretive turn: cartographic method, consideration of human and non-human actors, and social commitments; in addition, situational analysis gathers discourse and agency studies, action and structure, image, text and context, history, and the present moment to analyze complex investigations.